The Concept of Honor in Contemporary Political Philosophy: A Critical and an Adaptational Argument - Karalius , Gintas (Politologija, 2022)
In spite of a growing number of contemporary publications in the field of political philosophy that are dedicated to the concept of honor and to it’s analysis, there still is a lack of a systemic presentation of the conceptual field of honor itself. Political theorists and philosophers that treat the subject of honor state out their definitions of honor and compare them with one another, yet a general overview of the competing definitions and their critical comparison is still a rarety. A systemic presentation of all prominent contemporary philosophical studies that treat the concept of honor is useful in two ways. It facilitates the understanding of the main arguments that determine different definitions of honor, as well as it identifies major polemical issues that set the diferent concepts of honor apart. This article suggests two main arguments – a critical and an adaptational – for interpreting and comparing the different concepts of honor in contemporary political philosophy. Structuring the conceptual field of honor with these two arguments offers an analytic tool for further analyses of honor that are based on concrete polemical issues. It also gives a new perspective to explain the reemergence of honor in contemporary political philosophy.
Keywords: honor; political philosophy; critical argument; democracy; adaptive argument